دراسة قياسية لمحددات نمو القطاع الصناعي في ليبيا باستخدام نموذج الانحدار الذاتي للفجوات الزمنية الموزعة المتباطئة. (Economic studies journal, 2018)
This study aimed to recognize of determinants of an agriculture sector growth in Libya (PROD), which represented in a financial aggregate of an agriculture public sector in Libya (FUND); the growth rate of value added of agriculture sector ) VAXGR); an aggregate Libyan exports (AEXPO); & The political and security stability (PS). Farther more, the study was passed on approach of Bound Tests to estimate a relationship in long and short run during 1990- 2017. In additional, the study was found out that there is a long relationship between (PROD) as depended variable and in-depended variables which represented in FUND; VAXGR; AEXPO; &PS, but in short run an absence any relationship among study variables.
Keywords: An Agriculture sector growth; a financial aggregate of an agriculture public sector; the growth rate of Value Added of agriculture sector; an aggregate Libyan Exports; The political and security stability